Perception of Farmers about Kisan Credit Card Scheme - Karthika Venugopal,; P.J. Boniface,; R. Sendilkumar, (Journal of Agricultural Extension Management, 2025)
In order to ensure a hassle-free system in dispensing credit to farmers, the concept of Kisan Credit Card (KCC) was introduced in 1998 and operated at the grass root level. This study was conducted with 60 KCC holders of Adat Farmer's Service Co-Operative Bank (A FSCB) in Adat village of Thrissur district. Eighty seven percent of KCC holders have agriculture as the mainstay of livelihood. Majority of the respondents opined that the interest rate and present credit limit of KCC was at a moderate level. Two thirds of the respondents expressed that procedural formalities were moderate for getting KCC and also to get credit in time. The Scheme was perceived as good by a majority of respondents